Penerapan Strategi Pembeljaran Word Square Untuk Meningkatkan Motivasi Belajar Pada Tema 6 Subtema 2 Kelas Iv Sd Negeri 2 Trucuk Klaten Tahun 2014/2015 - NURDINI, DESI KUSUMA; , Muhroji (2015)
This study aims to increase students' motivation on the theme of 6 subtema 2 Elementary School sixth grade 02 Trucuk Klaten with word learning strategy square. Research diilakukan in SD Negeri 2 Klaten Trucuk. The study subjects were students of class IV which consists of 31 students. Data collection technique used observation, testing, documentation, and interviews. The validity of the data used triangulation techniques and resources. Results of the study visits of motivation and learning outcomes. Motivation to learn is shown in: (1) Prior to action known to enthusiastic students in receiving lessons from menjdi 25.80% 48.39% rise in the first cycle of action, and rose 80.64% on the action sklus II. (2) The willingness of students to listen to the explanation of the teacher is 19.35% rising to 41.93% in the first cycle of action, and rose 87.10% on the action sklus II. (3) Courage answered questions from teachers, namely 25.80% rising to 51.61% in the first cycle of action, and rose 77.42% on the action sklus II. (4) willingness to do the exercises given by the teacher, ie 29.03% rising to 58.06% in the first cycle of action, and rose 90.32% on the action sklus II. Increased student motivation is also followed by an increase in learning outcomes can be seen from the average score of the class before action values ​​obtained 64.68 rose to 72.06 in the first cycle and 81.19 in the second cycle. Prosentasse student test results before action 22.58% rising to 58.06% in silkus I and 90.32% in the second cycle.